A chemical study of the glycoside of Plumiera acutifolia Ait. (Family Apocynaceae) - Montojo, Corazon P.
The fresh bark of the plant Plumiera actutifolia Ait. (Fam. Apocynaceae) was found to contain the bitter principle, plumieride. The sample was analyzed and subjected to thin layer chromatogrphy, column chromatography and spectrophotometry.